Organo - mineral fertilization of wheat: impact on growth and N - recovery using 15N - stable isotope (Bangladesh Journal of Botany, 2018)
Investigation was carried out to follow up the effect of organo-mineral fertilizers on yield of wheat plants grown on sand soil using 15N stable isotope. Dry matter accumulation of wheat straw yielded 14.70 g/pot and grains yielded 12.72 g/pot with application of 50% As + BF. The highest values of N-uptake by straw and grains were 144.08 mg N/pot and 320.54 mg N/pot, respectively when treated with 50% As + BF. Portions of different N sources i.e. Nitrogen derived from fertilizer (% Ndff), nitrogen derived from air (% Ndfa) and fertilizer use efficiency (% FUE), gained by grains were (% 28.20), (% 19.70) and (% 34.31) as affected by addition of (50% ammonium sulphate (As) + Bio fertilizer, (25% rice straw (Rs) + 25% As + BF) and ( 25% chicken manure (CM) + 25% As + BF), respectively.